Antibiotic resistance of Escherichia coli isolated from captive Bengal tigers at Safari parks in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: The present study was carried out to assess the antibiotic resistance and to identify the resistance genes in Escherichia coli from captive Bengal tigers at two Safari parks in Bangladesh.Materials and Methods: A number of 24 environmental fecal swab samples of Bengal tigers were collected from two different Safari parks in Bangladesh. For the isolation of E. coli, samples were submitted to a number of bacteriological screening and biochemical tests. The antibiotic susceptibility of E. coli isolates was determined by disk diffusion method.Results: Results demonstrated that 18 environmental fecal samples were positive to E. coli in bacteriological screening and biochemical test. The overall prevalence of E. coli in Bengal tiger was 75% (n = 18/24). The antibiogram study unveiled that all the isolates were resistant to ampicillin. Sulfamethoxazole-trimethoprim, nalidixic acid, and tetracycline were 89% (n = 16/18) resistant. On the contrary, 100% (n = 18/18) of the isolates were sensitive to colistin sulfate. blaTEM was detected in 78% (n = 14/18) ampicillin-resistant isolates, whereas sul2 was found in 31% (n = 5/16) of the sulfamethoxazole-trimethoprim-resistant isolates.Conclusion: This study, first time in Bangladesh, highlights a significant proportion of environmental fecal samples from captive Bengal tigers at Safari parks harboring antibiotic resistant E. coli. Transmission of resistant E. coli from Bengal tigers to humans and the environment could pose a public health risk at Safari parks in Bangladesh.J. Adv. Vet. Anim. Res., 6(3): 341-345, September 2019